2015
DOI: 10.1038/nn.4140
|View full text |Cite
|
Sign up to set email alerts
|

Anchoring and synaptic stability of PSD-95 is driven by ephrin-B3

Abstract: Summary Organization of signaling complexes at excitatory synapses by Membrane Associated Guanylate Kinase (MAGUK) proteins regulates synapse development, plasticity, senescence, and disease. Post-translational modification of MAGUK family proteins can drive their membrane localization, yet it is unclear how these intracellular proteins are targeted to sites of synaptic contact. Here we show using super-resolution imaging, biochemical approaches, and in vivo models that the trans-synaptic organizing protein, e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
72
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(74 citation statements)
references
References 55 publications
1
72
0
Order By: Relevance
“…How PSD-95 itself docks onto postsynaptic sites has been unclear. Ephrin B3 has been previously implicated in this process (91), although it is unclear if it would be present at high enough levels to mediate postsynaptic anchoring of the highly abundant PSD-95. Instead, postsynaptic anchoring of PSD-95 and, consequently, of AMPARs has been shown to require -actinin, which is highly enriched in spines and binds to the N-terminal 13 residues of PSD-95 (92).…”
Section: Postsynaptic Anchoring Of Ampars By -Actininmentioning
confidence: 99%
“…How PSD-95 itself docks onto postsynaptic sites has been unclear. Ephrin B3 has been previously implicated in this process (91), although it is unclear if it would be present at high enough levels to mediate postsynaptic anchoring of the highly abundant PSD-95. Instead, postsynaptic anchoring of PSD-95 and, consequently, of AMPARs has been shown to require -actinin, which is highly enriched in spines and binds to the N-terminal 13 residues of PSD-95 (92).…”
Section: Postsynaptic Anchoring Of Ampars By -Actininmentioning
confidence: 99%
“…On neuronal activity, PSD-95 can be recruited to synaptic regions, as observed in the visual cortex after eye opening, which underlies activity-dependent synapse maturation (29,40); however, how activity drives the synaptic transport of PSD-95 during development remains elusive. The synaptic localization of PSD-95 can be regulated by its posttranslational modifications, including phosphorylation and palmitoylation, as well as by molecular binding with ephrin-B3 (10,(41)(42)(43). In this study, using a small interfering peptide that specifically inhibits liprinα1 phosphorylation, we have shown that inhibition of liprinα1 phosphorylation promotes PSD-95 clustering and its synaptic localization through enhanced interaction between these proteins.…”
Section: Discussionmentioning
confidence: 71%
“…To test this, we used a previously described assay in which DIV6-9 neurons are treated with soluble activated ephrin-B2 for 45 min to induce the surface interaction between EphB2 and the NMDAR 13,17,19 . The colocalization of transfected EGFP-GluN1 and endogenous EphB2 was quantified using custom macros 19,45 . Ephrin-B2 activation resulted in clustering of EphB2 in all conditions (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…FRAP analysis. EGFP intensity of bleached puncta and three randomly selected unbleached puncta were quantified for each time point by selecting the regions of interest (ROIs) around selected puncta in every image in the time series 45 . The unbleached puncta served as a control for the photobleaching during acquisition.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation